The Relationship of Economic Growth with Human Development and Electricity Consumption in Indonesia - Maqin, R. Abdul; Sidharta, Iwan (International Journal of Energy Economics and Policy, 2017)
The importance of human resource development is one of the goals of sustainable national development as well as the increasing availability of electricity consumption. This study aims to determine the relationship between gross domestic product with human development and electricity consumption in Indonesia. Descriptive analysis method to describe the relationship between gross domestic product growth with human development and electricity consumption. Data used from united nations development programme (UNDP). The results showed that there was a positive correlation between gross domestic product with human development and electricity consumption in Indonesia. Keywords: Gross Domestic Product, Human Development, Electricity Consumption. JEL Classifications: O13, O14, O15